2018
DOI: 10.1021/acsami.8b10527
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nanomaterials as Highly Efficient Inhibitors of Cellular Hepatic Fibrosis

Abstract: Chronic liver dysfunction usually begins with hepatic fibrosis. To date, no effective anti-fibrotic drugs have been approved for clinical use in humans. In the current work, titanium dioxide (TiO) nanoparticles (NPs) and silicon dioxide (SiO) NPs are used as active inhibitors with intrinsic chemico-physico properties to block fibrosis and the associated phenotypes through acting on hepatic stellate cells (HSCs, the liver machinery for depositing scar tissues seen in fibrosis). Using LX-2 cells as the HSC model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“…In particular, TiO 2 NPs induce lysosomal degradation of the TGFβ receptor complex (TβRI/II), and thereby downregulate the expression of TGFβ-target genes. TiO 2 NPs and silicon dioxide (SiO 2 NPs) were able to suppress ECM production, blocking the effect of TGFβ in cells implicated in liver fibrosis [55].…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…In particular, TiO 2 NPs induce lysosomal degradation of the TGFβ receptor complex (TβRI/II), and thereby downregulate the expression of TGFβ-target genes. TiO 2 NPs and silicon dioxide (SiO 2 NPs) were able to suppress ECM production, blocking the effect of TGFβ in cells implicated in liver fibrosis [55].…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…Although further studies are required, we speculate that phosphonate-capped UCNPs can escape the endothelium and reach the skeleton via a mechanism known as nanomaterial induced endothelial leakiness. In this process, nanomaterials enter and enlarge the nanosized gaps between microvascular capillary endothelial cells favouring their leakage to other tissue sites [29,30].…”
Section: Biodistribution Study By Radiolabeling Ucnpsmentioning
confidence: 99%
“…The results demonstrate the effectiveness of fluorescent SiNPs for the imaging-guided co-delivery of siRNA and DOX for therapy of MCF-7/ADR cells, and pave the way for the development of nanomedicines for MDR cancer cells. Of note, although silicon is distinguished by its low-or non-toxicity, numerous pioneering studies conducted by Professor Leong have revealed that nanoparticles may induce endothelial leakiness [37][38][39][40]. Therefore, further understanding of the behavior of SiNPs and SiNP-DOX/siRNA nanocomposites in vivo requires further investigation for their potential clinical application.…”
Section: Discussionmentioning
confidence: 99%